New Ways of Using Well Construction Reports for Hydrostratigraphic Analyses. Issue 1 (2nd March 2015) - Dunkle, Kallina M.; Anderson, Mary P.; Hart, David
Abstract: Hydrostratigraphic models require subsurface data. Those data can be gleaned from Well Construction Reports (WCRs) if the reports are properly reviewed and processed. In the United States, WCRs or similar documents are generally required to be submitted to a state agency. The quality of those reports varies considerably and depends on the water well contractor's level of geologic knowledge. Nevertheless, these types of reports are usually the largest available subsurface data set. We present two examples from Wisconsin, each of which had approximately 2000 WCRs, to demonstrate a variety of new applications of WCRs including obtaining information about the depositional environment; selecting sites to perform surface geophysical measurements; and creating three‐dimensional hydrostratigraphic models for groundwater modeling.